1995
DOI: 10.1159/000176904
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cigarette Smoking to the Severity of Coronary and Thoracic Aortic Atherosclerosis

Abstract: We studied the relationship of cigarette smoking to the severity of coronary and thoracic aortic atherosclerosis in 116 men who received coronary angiography and transesophageal echocardiography. Severity of coronary atherosclerosis was assessed in terms of Gensini’s score (GS), and that of thoracic aortic atherosclerosis was assessed by the average sclerotic length (ASL) and average sclerotic area (ASA). The plasma fibrinogen levels were significantly positively correlated with smoking, and fasting blood suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
1
22
1
1
Order By: Relevance
“…17 These studies suggest that each risk factor may not affect aortic wall thickness homogeneously. [10][11][12][13][14][15][16][17] Increasing age and hyperlipidemia are associated with a more significant thickening of the descending TA; however, there is no significant association between TA IMT and other risk factors (hypertension, diabetes mellitus, and smoking) in our study. Our results are somewhat different from those in previous reports regarding aortic wall thickness and the involvement of risk factors.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…17 These studies suggest that each risk factor may not affect aortic wall thickness homogeneously. [10][11][12][13][14][15][16][17] Increasing age and hyperlipidemia are associated with a more significant thickening of the descending TA; however, there is no significant association between TA IMT and other risk factors (hypertension, diabetes mellitus, and smoking) in our study. Our results are somewhat different from those in previous reports regarding aortic wall thickness and the involvement of risk factors.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results are somewhat different from those in previous reports regarding aortic wall thickness and the involvement of risk factors. 10,[15][16][17] While the population in our study consisted of 85 patients with significant CAD, the population in previous studies 10,[15][16][17] had no significant CAD. This, in addition to the racial difference, may explain the different results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the general population aged 45 years or older, 25.6% of the subjects had atherosclerosis in the aortic arch. 6 It has been reported that factors associated with ACL include age, 1,7 cigarette smoking, 1,8,9 hypertension, 10 diabetes mellitus 11 and coronary artery disease. 12,13 Less invasive methods have recently been developed to examine systemic atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Age is a wellknown predictor of the development of atherosclerosis on the whole [18][19][20] and aortic atherosclerosis in part [21][22][23][24] . There are also some data in the literature showing that smoking is independently connected with both the development and progression of aortic atherosclerosis [25][26][27][28] . According to our data, there is no correlation between other routine vascular risk factors and aortic atheromas.…”
Section: Discussionmentioning
confidence: 99%